Life-Cycle Assessment of Algae Renewable Diesel: Influence of Alternative Uses for Lipid-Extracted Algae - Shi, Rui; M. Handler, Robert; R. Shonnard, David (Current Biotechnology, 2016)
Background: Microalgae is considered a promising biofuel feedstock. When algae oil is extracted for fuel production, a significant portion of the lipid-extracted algae (LEA) generated as a co-product is generally re-used on site as a source of energy and nutrients. However, LEA may also be used for other purposes, including as a substitute for animal feeds. Methods: This life cycle assessment (LCA) study investigated the greenhouse gas (GHG) emission impacts of algae biofuel when the LEA co-product is used as a 1:1 (mass basis) substitute for soybean meal, rapeseed meal, fishmeal, or trout feed. All algae cultivation nutrients lost in LEA export were replaced with chemical fertilizers; electricity and heat previously generated on-site were replaced with US grid electricity and with natural gas heat. Important trade-offs were assessed in terms of GHG emissions for algae hydrotreated renewable diesel with LEA displacement credits for the different feed ingredients. Results: This LCA study indicated that the benefit from displacing animal feed does not outweigh the incremental burdens associated with replacing the energetic and nutrient requirements that LEA currently satisfies, resulting in higher GHG emissions for the algae biofuels life cycle. Conclusion: This study demonstrates the importance of decisions made throughout the full value chain of a product in determining the environmental impact of a product, given the regulatory pressure to develop low-carbon fuels.
Keywords: lipid-extracted algae